The Effect of Job Satisfaction on Turnover Intention of Food and Beverage Service Employees at Alila Seminyak Bali - I Gusti Gede Anggareksa Putra Mulyawan; I Gusti Ngurah Agung Suprastayasa; I Gusti Agung Gde Witarsana; Luh Putu Kartini (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2021)
Abstract Purpose: This study aims to examine the effect of job satisfaction on turnover intention of food and beverage service employees and to investigate possible areas of improvement to establish job satisfaction on overcoming turnover intention. Research methods: The job satisfaction is measured with a simplified JDI Model, and the turnover intention is measured with Mobley et al.’s Turnover Intention Heuristic Model. The research used quantitative and qualitative methods with a questionnaire and semi-structured interview as the instrument. The analysis includes a correlation test, the classic assumption test, and a simple linear regression test. Results and discussions: The result shows that job satisfaction has a significant negative effect on employee turnover intention. The ability of job satisfaction variables to explain the variance of turnover intention variable was moderate. Demographic factors such as age and academic education are among the most significant factors to influence turnover intention. Three areas of improvement to establish job satisfaction on overcoming turnover intention were addressed. Keywords: job satisfaction, turnover intention, human resources